Decision to Purchase Halal Labeled Salt in Kota Juang District, Bireuen Regency, Aceh Province - Ramziana Fitri; Yusriana Yusriana; Zalniati Fonna Rozali; Cut Nilda; Novia Mehra Erfiza (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
The purpose of this study was to determine the presence of halal labeling on salt packaging on salt purchasing decisions in Kota Juang District, Bireuen Regency, Aceh Province. This study used survey method and purposive sampling. Data sources are primary data and secondary data. Data collection techniques through recording, interview and observation. This study uses a linear regression model to determine the effect of halal labeling on consumer purchasing decisions for salt. Hypothesis proving uses statistical tests simultaneously (F test) and partially (T test). The results showed that the tcount value (14.086) ttable (1.984) with a significant value of T (0.000) 0.05, so it can be concluded that the halal label affects the decision to purchase salt in Juang City, Bireuen.